Environmental perspective on tsunami disaster mitigation and its implications: a critical review - Septa Anggraini; Raldi Hendro T. Koestoer; Daryono (Institute for Advanced Science, Social, and Sustainable Future, 2023)
Tsunamis are one of the deadliest and most destructive natural disasters, having the potential to cause significant damage to the environment and society. Therefore, tsunami hazard modeling becomes very important in disaster risk management and environmental protection. Tsunami evacuation isan important and effective effort that must be carried out to save the community when a tsunami occurs. The aim of this study is to review the environmental perspective on the tsunami evacuation plan in terms of environmental, social, and economic aspects, along with their implications. Aqualitativedescriptive study was carried out through a literature review by comparing case studies in various coastal areas affected by the tsunami. Environmental factors play an important role in the results of tsunami modeling which will form the basis for evacuation plans.Social and economic aspects also play a role in people's behavior when evacuating, reviewed and observed, in order to produce an effective and sustainable evacuation plan.